2003
DOI: 10.1583/1545-1550(2003)010<1031:doirac>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of In-Stent Restenosis After Carotid Angioplasty: A Case-Control Study

Abstract: The present study, far from being exhaustive on the subject, indicates that patients who develop restenosis after carotid endarterectomy are also prone to develop restenosis after CAS; moreover, although strongly recommended for postsurgical restenosis, CAS carries a greater risk of in-stent restenosis in this subgroup, thus reducing the benefits of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 35 publications
2
28
0
Order By: Relevance
“…52 Finally, there still is the need for identifying specific risk factors for the development of restenosis after CAS. Some studies have identified advanced age, 18 female gender, 18 hyperglycemia, 53 previous treatment with a CEA, 54 and increased serum levels of acute-phase reactants 21 as potential risk factors for the development of a restenosis after CAS; however, the definitive role of these factors remains to be elucidated in larger trials.…”
Section: Discussionmentioning
confidence: 99%
“…52 Finally, there still is the need for identifying specific risk factors for the development of restenosis after CAS. Some studies have identified advanced age, 18 female gender, 18 hyperglycemia, 53 previous treatment with a CEA, 54 and increased serum levels of acute-phase reactants 21 as potential risk factors for the development of a restenosis after CAS; however, the definitive role of these factors remains to be elucidated in larger trials.…”
Section: Discussionmentioning
confidence: 99%
“…Stent restenosis is one of the most important factors affecting the long-term effects of carotid stent angioplasty (Khan et al, 2003;Setacci et al, 2003;Gurm et al, 2008;Moreira et al, 2012). Restenosis is caused by the hyperplasia of the smooth muscle cells or endomembrane, rather than by the atherosclerosis plaque.…”
Section: Discussionmentioning
confidence: 99%
“…The in-stent stenosis rate for bare metal stents in larger studies has been estimated at 4-5% 15 . Maras et al 13 reviewed 20 patients of traumatic pseudoaneurysms treated with covered stent grafts and found a 15% occlusion rate.…”
Section: Casementioning
confidence: 99%